Isolation, Characterization, and Antibiogram Profile of Fungi from Spoilt Bread - Aishatu Suleiman; AbdulAzeez Mumsiri Abaka; Raymond Istifanus (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
AbstractBread is a staple food in Nigeria, but its high perishability due to fungal spoilage leads to significant economic waste and public health risks from potential mycotoxin production. This study aimed to isolate, identify, and evaluate the antifungal susceptibility of fungi responsible for spoiling bread in Adamawa State, Nigeria. Twelve bread samples were collected from local vendors in Girei and Yola North. Fungi were isolated on Potato Dextrose Agar (PDA) and identified using a polyphasic approach combining morphological characteristics. An antifungal susceptibility test was performed using the agar dilution method to determine the Minimum Inhibitory Concentration (MIC) of ketoconazole, fluconazole, and itraconazole against the isolates. The mycological analysis revealed a community dominated by Aspergillus sp., which was present in over 90% of viable samples. Rhizopus spp. were frequently isolated as secondary contaminants, while Mucor, Fusarium, and Penicillium species were less common. Quantification showed high fungal loads, ranging from 4.1 × 10? to 3.9 × 10? CFU/mL. The antifungal susceptibility profiles revealed widespread resistance to fluconazole and itraconazole among the isolates. Aspergillus and Rhizopus were resistant to both (>100% MIC), while Mucor was resistant to fluconazole. In contrast, ketoconazole was the most effective agent, with all tested genera showing sensitivity at concentrations between 20% and 80% MIC. The findings confirm the dominance of Aspergillus in bread spoilage within the study area and highlight a concerning level of resistance to common azole antifungals. The demonstrated efficacy of ketoconazole suggests it could be a viable alternative for preservation. This study provides critical data for developing targeted antifungal strategies and evidence-based policies to extend the shelf life of bread, reduce economic losses, and mitigate mycotoxin-related health risks for consumers in Nigeria.